Immunomodulatory effects of extracellular vesicles in glioblastoma - Low, Johannes Jun Wei; Sulaiman, Siti Aishah; Johdi, Nor Adzimah; Abu, Nadiah (Frontiers in Cell and Developmental Biology, 2022)
Glioblastoma (GB) is a type of brain cancer that can be considered aggressive. Glioblastoma treatment has significant challenges due to the immune privilege site of the brain and the presentation of an immunosuppressive tumor microenvironment. Extracellular vesicles (EVs) are cell-secreted nanosized vesicles that engage in intercellular communication via delivery of cargo that may cause downstream effects such as tumor progression and recipient cell modulation. Although the roles of extracellular vesicles in cancer progression are well documented, their immunomodulatory effects are less defined. Herein, we focus on glioblastoma and explain the immunomodulatory effects of extracellular vesicles secreted by both tumor and immune cells in detail. The tumor to immune cells, immune cells to the tumor, and intra-immune cells extracellular vesicles crosstalks are involved in various immunomodulatory effects. This includes the promotion of immunosuppressive phenotypes, apoptosis, and inactivation of immune cell subtypes, which affects the central nervous system and peripheral immune system response, aiding in its survival and progression in the brain.